Beliefs About Help Seeking for Mental Disorders: Findings From a Mental Health Literacy Study in Singapore - Picco, Louisa; Abdin, Edimansyah; Chong, Siow Ann; Pang, Shirlene; Vaingankar, Janhavi A; Sagayadevan, Vathsala; Kwok, Kian Woon; Subramaniam, Mythily (Psychiatric services (Washington, D.C.), 2016)
This study investigated beliefs about help seeking, treatment options, and expected outcomes for alcohol abuse, dementia, depression, obsessive-compulsive disorder (OCD), and schizophrenia, by using a vignette-based approach. The Mind Matters study was a comprehensive, population-based, cross-sectional survey conducted among Singapore residents (N=3,006) ages 18 to 65 to establish the level of mental health literacy. Questions were asked about whom the person in the vignette should seek help from, the likely helpfulness of a broad range of interventions, and the likely outcome for the person in the vignette with and without appropriate help. "Talk to family or friends" was the most common source of help recommended for alcohol abuse (30.1%), depression (54.2%), and schizophrenia (21.5%), and "see a doctor or general practitioner" was the most recommended for dementia (53.8%) and OCD (26.8%). Help-seeking preferences were significantly associated with age, gender, ethnicity, and income and with having a personal experience of or knowing someone with a mental disorder similar to that described in the vignette. Respondents rated seeing a psychiatrist as the most helpful intervention (88.4%) and dealing with the problem on his or her own as the most harmful (64.6%). Most respondents (79.3%) indicated that the condition of the person in the vignette would worsen if appropriate help was not sought. Most respondents recommended seeking help for mental disorders from informal sources, such as family and friends. Targeted intervention strategies to improve mental health literacy related to help seeking, treatment beliefs, and effectiveness of evidence-based treatments are needed in Singapore.